Low-ohmic-contact-resistance V-based electrode for n-type AlGaN with high AlN molar fraction. (25th April 2016) - Mori, Kazuki; Takeda, Kunihiro; Kusafuka, Toshiki; Iwaya, Motoaki; Takeuchi, Tetsuya; Kamiyama, Satoshi; Akasaki, Isamu; Amano, Hiroshi
Abstract: We investigated a V-based electrode for the realization of low ohmic-contact resistivity in n-type AlGaN with a high AlN molar fraction characterized by the circular transmission line model. The contact resistivity of n-type Al0.62 Ga0.38 N prepared using the V/Al/Ni/Au electrode reached 1.13 × 10 −6 Ω cm 2 . Using this electrode, we also demonstrated the fabrication of UV light-emitting diodes (LEDs) with an emission wavelength of approximately 300 nm. An operating voltage of LED prepared using a V/Al/Ni/Au electrode was 1.6 V lower at 100 mA current injection than that prepared using a Ti/Al/Ti/Au electrode, with a specific contact resistance of approximately 2.36 × 10 −4 Ω cm 2 for n-type Al0.62 Ga0.38 N.